Descriptive Study of Contact Dermatitis to Sponge Production Workers in Esterindo Factory - Djap Hadi Susanto; Melda Suryana; Seung Hee Lee (Jurnal MedScientiae, 2022)
Contact dermatitis is a major health problem of skin disease for workers who have a history contact with chemicals or irritants. This disease can usually be found in industry, plantations or agriculture. In 2020, from 27,000 workers resulted prevalence rate of dermatitis was around 9.8%. The aim of this study is to describe the incidence of contact dermatitis in sponge foam production workers at Esterindo factory on the last week of August until the first week of September, 2021. This research is a descriptive study with a method of cross-sectional study. TBased on the results, workers with contact dermatitis were 14 workers, 18,4%. The most common groups who got contact dermatitis were the age group of 40-49 years (31,8%), women (15,7%), pasting sponge group (33,3%), average working period in 2 years and a half month, in average 5 days of working and an average of 7 hours working in a day. The total workers who has contact dermatitis in Esterindo factory are 14 workers (18,4%). The incidence of contact dermatitis in Esterindo factory could be affected from discipline of workers in the use of personal protective equipment, characteristics of activities in each worker, medical history and history of skin diseases.